Literary Scholars’ Disciplinary Literacy Orientations - Rackley, Eric D. (Language and Literacy / Langue et littératie, 2021)
This study examines how four university-based literary scholars in the United States read literary texts. Findings suggest that the scholars used four related literary literacy orientations in their reading: They attended to their affective experiences with literature, built recursive interpretations of literature, contextualized literature, and recognized and managed literary complexity. As broad-level disciplinary ways of navigating literature, these literary literacy orientations included the scholars’ meaning-making practices as well as their beliefs, feelings, and attitudes about literature and making sense of it. Findings support and build upon existing scholarship on English disciplinary literacies and offer paths for further research.